The European radiation dosimetry group – Review of recent scientific achievements. (March 2020) - Rühm, W.; Ainsbury, E.; Breustedt, B.; Caresana, M.; Gilvin, P.; Knežević, Ž.; Rabus, H.; Stolarczyk, L.; Vargas, A.; Bottollier-Depois, J.F.; Harrison, R.; Lopez, M.A.; et al.
Abstract: The European Radiation Dosimetry Group (EURADOS) is a network of organizations and scientists promoting research and development in the dosimetry of ionizing radiation, contributing to harmonization in dosimetry practice across Europe, and offering education and training in areas relevant for dosimetry. As a registered non-profit association under German law, EURADOS is currently running eight active working groups (WGs): WG2 on "Harmonization of Individual Monitoring", WG3 on "Environmental Dosimetry", WG6 on "Computational Dosimetry", WG7 on "Internal Dosimetry", WG9 on "Dosimetry in Radiotherapy", WG10 on "Retrospective Dosimetry", WG11 on "Dosimetry in High-Energy Radiation Fields", and WG12 on "Dosimetry in Medical Imaging". This paper presents recent scientific results obtained within these working groups, and additionally highlights the role of EURADOS as an organization which contributes to the development of a systematic strategy of radiation protection research in Europe.